Tax Expenditures, Reform, and Distributive Justice - Sugin, Linda (Columbia Journal of Tax Law, 2012)
Tax reform is coming, and it will be an important part of any plan to avert national fiscal disaster. The President’s Fiscal Commission recently presented a proposal for comprehensive tax reform that will form the basis for serious legislative discussion. At the center of that proposal is elimination of “tax expenditures,” which are provisions in the tax law that operate like direct government spending. They include the charitable deduction, the home mortgage interest deduction, the exclusion for employer-provided health insurance, the child credit, the earned income credit, education credits and deductions, the tax preference for retirement savings accounts like IRAs and 401(k) plans, and dozens of others. This article argues that elimination of tax expenditures is a flawed approach to tax reform. Tax expenditures are not an undifferentiated mass, but reflect a wide variety of federal policies, each of which requires independent evaluation. Before policymakers can decide whether to abolish tax expenditures, they need to know a lot more than the tax expenditure budgets currently reveal about what tax expenditures do, who benefits from them, and how much revenue could be raised by their repeal. They also need to decisively identify which provisions are tax expenditures, a perennial source of disagreement. This article argues that proposals to repeal tax expenditures reflect a normative preference for efficiency over equity, the traditional twin goals of tax policy, squandering the tax law’s unique role in economic justice.